Dunajski anatom Joseph Hyrtl (1810-1894) - Zupanič Slavec, Zvonka (Medicinski razgledi, 1996)
Doctor Joseph Hyrtl, a prominent scientist and teacher, descriptive and comparative anatomist, hystologist and physiologist, medical historian and a sensitive medical philologist at the Prague and Vienna medical faculties died a century ago. His collection of anatomic preparations, a result of 40 years of his life, is of invaluable worth. It is now on display at the Institute for the History of Medicine at Vienna University and the Perchtoldsdorf museum near Vienna. Hyrtl was also an excellent pedagogue and rhetorician, who educated many generations of medical students at the Prague and Vienna faculties. In the years 1845-1874 many Slovene, Croatian and other Slavic medical students attended his lectures on anatomy. He gained high popularity among his students and the majority of them found his lectures very refreshing and ingenious. He wrote an excellent textbook on anatomy for students and doctors which saw 20 editions published during his lifetime. In addition, he wrote a whole range of books on comparative anatomy and medical terminology. He was also a great humanitarian and benefactor.
Keywords: Hyrtl, Joseph, 1810-1894; biografije